BCT493: Construction safety and health / College of Built Environment - UiTM, College of Built Environment (UiTM, 2018)
The course develops an awareness of the paramount importance of safety and health in construction. It covers the understanding of development of construction safety and health policy, plans and procedures. The course includes identifying the hazards and understanding the risk assessment and control.